Assessment in Neurologic Education - Jones, Lyell K., Jr. (Seminars in Neurology, 2018)
Neurology trainee assessment is a required component of the education feedback loop, allowing programs and trainees to measure their progress toward established educational goals. In the era of competency-based medical education, assessment systems should be designed to inform decisions about each trainee's acquisition of the many competencies required for independent clinical neurology practice. In addition to the need to inform trainees and programs regarding trainee performance, assessment systems must be equipped to satisfy requirements established by accrediting bodies. Educational goals should be thoughtfully established prior to assessment system design to ensure that assessment priorities align with the overall goal of equipping graduates to deliver high-quality neurologic care. This article provides an overview of modern principles of medical education as they can be applied to neurologic education, complemented by practical recommendations for neurologic educators to develop or improve assessment systems within their own training programs.
Keywords: assessment; neurologic education; competency-based medical education; feedback; evaluation